Investigating the demographic and attitudinal predictors of rape myth acceptance in U.K. Police officers: developing an evidence-base for training and professional development. Issue 1 (2nd January 2019) - Murphy, Anthony; Hine, Benjamin
ABSTRACT: Efforts to understand rape myth acceptance (RMA) as a cognitive framework in police, unifying key cognitive/attitudinal and demographic factors into one coherent model, are lacking. Using a cross-sectional survey design, predictors of RMA were assessed by linear hierarchical regression, including demographic (age, length of service, gender, experience of specialist rape investigation training) and attitudinal factors (hostility towards women, sexist attitudes, and explicit power/sex beliefs) among officers from a large U.K. police force ( N = 912). The final model explained 44% of variance in RMA. Gender and previous specialist training significantly predicted RMA, but to a much lesser extent than attitudinal variables, which explain 42% of RMA variance. Only specialist rape investigation training remained significant when attitudinal variables were added. The greater contribution from attitudinal variables suggests that efforts to address RMA in officers must consider the broader attitudinal structures underpinning RMA. Findings highlight implications for evidence-based training for rape investigators.